MENTAL HEALTH NURSING . (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Mental health nursing, also known as psychiatric nursing, is a specialized field of nursing practice that involves the care of individuals with a mental health disorder to help them recover and improve their quality of life. Mental health nurses have advanced knowledge of the assessment, diagnosis, and treatment of psychiatric disorders that helps them provide specialized care. They typically work alongside other health professionals in a medical team with the aim of providing the optimal clinical outcomes for the patient.